Dental Extraction of Myasthenia Gravis Patient with Multiple Systemic Implications: A Case Report - Sami Sowairi,; Lujain A. Homeida, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Myasthenia gravis is a chronic autoimmune neuromuscular disorder that results in progressive skeletal muscle weakness. Dental management of patients diagnosed with myasthenia gravis is challenging. In this article, a case report of dental extraction in a 75- year old myasthenia gravis patient with other medical problems complicating his condition is presented. The management of such cases in dental clinics will be discussed. When planning a treatment, dentists must be aware of facial and masticatory muscle weakness that affects majority of patients. Myasthenia gravis patients usually suffer from the long-term effect of the disease on different body systems, mainly respiratory and endocrine systems. Moreover, the drugs used in the management of myasthenia gravis have side-effects that might interfere with the dental treatment or interact with dental medication. Patients with myasthenia gravis require specific dental treatment planning in order to avoid exacerbation and myasthenic crisis during the dental treatment.